Obstructive airway disease in 46–65‐year‐old people in Busselton, Western Australia, 1966–2015. Issue 5 (19th March 2018) - Musk, Arthur (Bill); Hunter, Michael; Hui, Jennie; Knuiman, Matthew W; Divitini, Mark; Beilby, John P; James, Alan
Abstract: Objective: To document the changing levels of tobacco smoking, respiratory symptoms, doctor‐diagnosed asthma, and lung function in Busselton adults aged 46–65 years over the past 50 years. Design, setting, participants: Repeated cross‐sectional population surveys (1966 to 2010–2015) of adults registered to vote in the Busselton shire, Western Australia, including a modified version of the British Medical Research Council questionnaire on respiratory symptoms. Main outcome measures: History of doctor‐diagnosed asthma and chronic obstructive pulmonary disease (COPD), tobacco smoking history, respiratory medications used, spirometry parameters (forced expiratory volume in one second [FEV1 ], forced vital capacity [FVC]). Results: The prevalence of tobacco smoking among men declined from 53% in 1966 to 12% in 2010–2015, and from 26% to 9% among women. The prevalence of ever‐smoking (ie, smokers and ex‐smokers) decreased from 80% to 57% for men but increased from 33% to 50% for women. The prevalence of doctor‐diagnosed asthma increased, as did the use of long‐acting bronchodilator aerosol medications by people with asthma and COPD. There have been no consistent changes in the prevalence of specific respiratory symptoms, but measures of lung function have significantly improved. Conclusions: Smoking rates declined as a result of changes in pricing, prohibitions on smoking and the feedback of survey results to Busselton participants. Significant improvements in lung function were measured, and it can be anticipated that the prevalence of other smoking‐related diseases will also decline.